2014
DOI: 10.1038/srep04155
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of short- and long-term association between a bacterial plant pathogen and its arthropod vector

Abstract: The dynamics of association between pathogens and vectors can strongly influence epidemiology. It has been proposed that wilt disease epidemics in cucurbit populations are sustained by persistent colonization of beetle vectors (Acalymma vittatum) by the bacterial phytopathogen Erwinia tracheiphila. We developed a qPCR method to quantify E. tracheiphila in whole beetles and frass and used it to assess pathogen acquisition and retention following variable exposure to infected plants. We found that (i) E. trachei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…We have shown that E. tracheiphila can survive and be retained in the alimentary canal of A. vittatum 4 days after inoculation. This is consistent with prior vector competence and bacterial retention studies (Shapiro et al 2014).…”
Section: Presence Of Pseudomonas Fluorescenssupporting
confidence: 90%
“…We have shown that E. tracheiphila can survive and be retained in the alimentary canal of A. vittatum 4 days after inoculation. This is consistent with prior vector competence and bacterial retention studies (Shapiro et al 2014).…”
Section: Presence Of Pseudomonas Fluorescenssupporting
confidence: 90%
“…More recently, Shapiro et al (2014) developed a real-time quan titative PCR assay to characterize pathogen acquisition and retention time by striped cucumber beetles. After 3-and 24-h acquisition access periods (AAP) on E. tracheiphila-mfected plants, they estimated bac terial populations in whole beetles and frass.…”
Section: Vector and Transmission Biologymentioning
confidence: 99%
“…For example, many pollinators likely transfer microbes between flowers during normal foraging that may directly affect other visiting insects, or indirectly alter traits determining floral attractiveness (Yang et al, McArt et al 2014, Ravoet et al 2014, Vannette and Fukami 2016, Rering et al 2018, Figueroa et al 2019). Some insect pollinators and herbivores encounter plant pathogens while feeding, and can then transmit these pathogens from infected to healthy plants (Raguso and Roy 1998, Alexandrova et al 2002, López-Villavicencio et al 2007, Degnan et al 2009, Shapiro et al 2012, Shapiro et al 2014, Mauck et al 2018, Shapiro and Mauck 2018, Cellini et al 2019). Yet, for almost all insect taxa, we still lack an understanding of the spatial and temporal diversity of microbes that insects are naturally exposed to, which microbes are able to persistently colonize insects as hosts vs. transiently pass through the digestive tract, and the impacts of different microbes on ecological interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate Eastern North America, both E. pruinosa and A. vittatum exclusively rely on domesticated plants grown in human managed agro-ecosystems as a food resource. Temperate Eastern North America is also the only region worldwide where A. vittatum transmits Erwinia tracheiphila Smith (Enterobacteriaceae), the causal agent of bacterial wilt of cucurbits, which causes millions of dollars annually in direct yield losses and indirect preventative measures (Shapiro et al 2014, Shapiro et al 2016, Shapiro et al 2018b). E. tracheiphila can persistently colonize the digestive tract of beetle vectors after beetles feed on the foliage of wilting, symptomatic plants (Rand and Enlows 1916, Rand and Cash 1920, Rand and Enlows 1920, Smith 1920, Shapiro et al 2012, Shapiro et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation